KINGYAW’S RECITING POEM ON AFRO-AMERICAN ACCENT: THE WORLD-ENGLISHES MOVEMENT - Wijayanti, Nurvita; Wilujeng, Panggio Restu (International Journal of Humanity Studies (IJHS), 2021)
Fanon in his book titled ‘Black Skin, White Masks’ says that no matter how smart black people may become, white people will always feel the sense of ‘inferiority’ in which black people speak Pidgin. The sense of imitation of imitating makes  the colonizer culture, in which the black people come across inferior from the white’s perspective. KingYaw’s YouTube video tries to break such a false perception. In his video, he talks the way black people have their unique accent It cannot be  compared to the Received Pronunciation (BrE). Therefore, this study aims to unravel the linguistic theory on language variation as a part of the World-Englishes movement. This study uses descriptive qualitative method by having one of KingYaw’s video performing and reciting a poem titled “Accent” that was uploaded in YouTube on December 17th, 2018. Post-colonialism allows the people to see the world without discrimination.